Tick-borne illness - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Varicella - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Trauma informed care - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Tracheostomy care - Borgognone, Kristen (School nurse resource manual: A guide to practice, 2020)
.SCHOOL NURSE RESOURCE MANUAL NINTH EDITION EVIDENCED-BASED POLICIES and PROCEDURES for SAFE STUDENT CARE. The School Nurse Resource Manual was created for school nurses as a quick reference on the many issues they encounter in their practice, and to assist them, their administrators and consulting physicians to develop consistent evidenced-based policies and procedures for safe student care. This ninth edition contains clinical guidelines that have been completely updated, expanded and revised to reflect current clinical guidelines for safe student care. ALL GUIDELINES ARE RESEARCHED, REFERENCED AND PEER REVIEWED.
Keywords: dept.nur

Summer Nursing Symposium: An Immersive Educational Program Inspiring Underrepresented Minorities for College and a Career in Nursing - Knickerbocker, Joshua; Krol, Maria; Bartlett, Andrew; Borgognone, Kristen; Martinez, Kelly (Hispanic Health Care International, 2025)
Keywords: Medical education; Medicine; Nurse education; Nursing; Psychology; Underrepresented Minority; dept.nur; peer-reviewed

Flu vaccinations: College campus not making the grade. A study of influenza vaccination at an urban public university. - Kreiger, Joan E; Zigmont, Victoria A.; Michalski, Carrie D; Borgognone, Kristen S (Journal of American college health : J of ACH, 2021)
Objective: Even healthy college students are vulnerable to severe complications associated with seasonal influenza (flu). Despite national directives to increase influenza vaccination compliance, college campuses remain woefully below national goals. This study aimed to identify factors correlated with the decision to voluntarily receive an influenza vaccine. Additionally, students’ reasons for non-vaccination were also examined. Participants: 1021 undergraduate students across four professional schools. Methods: A representative cross-sectional survey was conducted at a public, urban university. Results: The survey measured self-reported influenza vaccination: an overall influenza vaccination rate of 38% was identified. Student characteristics associated with increased influenza vaccination included students’ enrollment in academic health disciplines; being female; human papillomavirus (HPV) vaccination; and no marijuana use in the last month. Barriers to influenza vaccination included contraindications, mistrust issues, and personal reasons. Conclusion: Universities that can identify facilitators and barriers to voluntary influenza vaccination can assist with program initiatives to improve influenza vaccination compliance rates. © 2021 Taylor & Francis Group, LLC.
Keywords: dept.hms; dept.nur; dept.pch; peer-reviewed